In-pile performance of end plug with different structure for SiC cladding - Yue, Huifang; Liu, Shichao; Xin, Yong; Li, Yuanming; Chen, Ping; Qiu, Xi (Frontiers in Materials, 2023)
The in-pile performance of SiC cladding with different kinds of end plug were studied. The effect of end plug structure on the mechanical performance of cladding was investigated. The results indicated that obvious stress concentration was appeared on the corner between cladding and end plug for all kinds of cladding. The cladding with scarf end plug possessed lowest hoop, axial and radial stress, which ensured the structure integrity of the fuel element. The cladding with butted and butted lap end plug suffered rather large axial stress, the maximum valve was up to 450 MPa at the end of life, which was higher than the yield strength of SiC ceramics. Scarf end plug can meet the requirements of the cladding, which may be used as end plug of fuel rod in the future.